PENGARUH NILAI TUKAR RUPIAH (KURS), INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2008-2014 - Muhammad Faisal Amrillah (VALUTA, 2016)
This research studies about stock returns of banking companies listed in Indonesia Stock Exchange. Specifically, this research wanted to assess the effects of macroeconomic indicators, exchange rates, inflation and economic growth on return stock of banking companies during the period 2008-2014. The method used in this research is path analysis with the sampling technique used purposive sampling. Data obtained from yahoo finance, economic indicators from Central Bureau of Statistics (BPS), and monthly report of Bank Indonesia. The results shows that the variables of exchange rate, inflation and economic growth have direct negative effect on stock returns. The study also found that the exchange rate and inflation variable have indirect effect on stock returns through economic growth.